The Influence of Think, Talk, and Write (TTW) Strategy towards Students' Descriptive Writing Mastery - Riandi, Riandi; Nurfaujiah, Siti (Universitas Mathla'ul Anwar Banten, 2018)
This research paper was aimed at investigating the influence of Think, Talk, and Write (TTW) stategy towards students’descriptive writing at 2nd grade students of MTS MA Cikaliung. The population of this research was 117. The researcher used simple random sampling to determine the sample. There were two classes taken as sample, VIII C as experimental class with 29 students, and VIII B as control class with 29 students too. This research paper employs the quantitave research design with characteristics of experimental research. The data collection method of this research used a test involving pre-test and post-test. After giving pre-test and post-test, the researcher found that the post-test score of experimental class was higher than the post-test score of control class, which were 2024 > 1731. It means that students’writing score was increase after treating by think, talk, and write strategy. Through calculating the t-test, the researcher also found that t-count was higher than t-table, which were 4.77 > 2.005. It means that there is significant influence of applying think, talk, and write strategy in teaching writing. The findings of this research show that it is significant for the teachers to choose the appropriate stategy for improving students’ writing mastery, particularly think, talk, and write strategy as mentioned above. It is also wise for the teachers to identify the students’ responses on the strategy used to determine which strategy is appropriate for them. The findings also expect others researcher to investigate the influence of this strategy on other students’ English skill.